Antagonistic effects of endostatin-vascular endothelial growth inhibitor chimeric recombinant adenovirus on homocysteine-induced vascular endothelial cells injury in vitro and in vivo. Issue 44 (November 2016) - Cui, Zhen-Tian; Liu, Jian-Ping; Yao, Jian-Min
Abstract: Background: The study is inclined to investigate the antagonistic effects of endostatin-vascular endothelial growth inhibitor chimeric recombinant adenovirus (Ad-hENDO-VEGI) on homocysteine (Hcy)-induced vascular endothelial cells (VECs) injury in vitro and in vivo. Methods: Human VECs cell line ECV304 was selected and infected with Ad-hENDO-VEGI. The LDH leakage, SOD activity, and MDA levels were measured by the automatic biochemical analyzer. Cell survival rate was counted by Trypanblau dying. The TNF-α and MCP-1 protein expressions were detected by ELISA assay. The protein expressions of fusion protein of Ad-hENDO-VEGI, nuclear factor kappa B p65 (NF-kappa B p65), and NF-kappa B inhibitor alpha (I-kappa B-α) were detected by Western blotting. A rat model of hyper-homocysteinemia was constructed. Thirty-six Wistar rats were randomly divided into 3 groups: the control group, the model group, and the Ad-hENDO-VEGI group. Serum Hcy levels in rats were measured with enzymatic cycling method. Endothelial vasodilation function was evaluated with the treatment of sodium nitroprusside and acetylcholine. Results: After Ad-hENDO-VEGI infection, high expressions (41 kD) of fusion proteins in ECV304 cells were observed. The injury severity of Hcy on ECV304 cells had a dose-dependent manner, and the injury reached a steady stage at 1.0 mmol/L. Thus, 1.0 mmol/L Hcy was selected for further experiments. With an increase of Ad-hENDO-VEGI in ECV304 cells after Hcy treatment, LDH leakage, MDA, TNF-α, MCP-1, and nuclear NF-kappa B p65 protein expression were gradually decreased, and cell survival rate, SOD activity, and I-kappa B-α protein expression were gradually increased. Compared with the control group, the model group had a higher Hcy level and attenuated vasodilator response. The Ad-hENDO-VEGI group exhibited a lower Hcy level and enhanced vasodilator response than the model group. Conclusion: These results indicated that Ad-hENDO-VEGI could down-regulate NF-kappa B p65 expression and suppress inflammatory response, thereby alleviating Hcy-induced VECs injury.